Estudio sobre el balance social como herramienta de gestión en las cooperativas de ahorro y crédito del segmento 1 en Ecuador en los periodos 2019 a 2021 - Aguirre Uribe, Rosa Elena (2023)
The purpose of this study is to analyze the application of the social balance sheet as an instrument for evaluating the compliance with social responsibility and the performance of credit unions in segment 1. By analyzing and comparing the social balance sheet models applied by the entities studied, similarities were observed between the models of the Cooperative Principles (ICA), the principles of the United Nations Organization (UN) Global Compact and Sustainable Development Goals (SDGs), which cover economic, social and environmental aspects for local development. Discussion of the results reveals the need for credit unions to determine the level of social responsibility applied and the possibility of creating a standard social balance sheet as part of cooperative management reports. The information presented was collected through the application of a mixed qualitative and quantitative methodology and multiple case study method, with the use of primary data sources and elaboration of data tables.